On Functions of Several Split-Quaternionic Variables. (13th March 2016) - Grantcharov, Gueo; Montoya, Camilo
Abstract : Alesker studied a relation between the determinant of a quaternionic Hessian of a function and a specific complex volume form. In this note we show that similar relation holds for functions of several split-quaternionic variables and point to some relations with geometry.